Bioethical principles in the context of the COVID-19 pandemic - Ñique Carbajal, Cesar (2021)
The worldwide spread of the COVID-19 pandemic has triggered an international sanitary crisis that many countries could not tackle. In our country the relationship among the health care professionals their patients and relatives has been affected, in part due to a disorganized governmental response to the pandemic that dictated incorrect treatment recommendations based on foreign experiences resulting in severe attempts against the individual dignity. On the other hand, the lack of resources, the rampant corruption and the poor resolution capacity for diagnosing cases leaded not only of knowing the magnitude of the pandemic in the country but also to discouragement among health care professionals who are at the frontline experiencing fear and vulnerability. We do believe that we need to rethink on the impact of the pandemic in the country as well as on the critical reforms needed in our health care system promoting integrated human care, following current bioethical models and personalized ethical principles in order to improve current medical practices during the COVID-19 pandemic.